Whole genome analysis and antimicrobial resistance of Neisseria gonorrhoeae isolates from Ghana - Agbodzi, Bright; Duodu, Samuel; Dela, Helena; Kumordjie, Selassie; Yeboah, Clara; Behene, Eric; Ocansey, Karen; Yanney, Jennifer N.; Boateng-Sarfo, George; Kwofie, Samuel Kojo; Egyir, Beverly; Colston, Sophie M.; et al. (Frontiers in Microbiology, 2023)
Gonorrhoea is a poorly controlled public health problem. With the global emergence and spread of resistance to first-line antibiotic treatment options, gonorrhoea threatens to be untreatable in the future. Therefore, this study performed whole genome characterization of Neisseria gonorrhoeae collected in Ghana to identify lineages of circulating strains and their phenotypic and genotypic antimicrobial resistance (AMR) profiles. Whole genome sequencing (WGS) was performed on 56 isolates using both the Oxford Nanopore MinION and Illumina MiSeq sequencing platforms. The Comprehensive Antimicrobial Resistance Database (CARD) and PubMLST Neisseria databases were used to catalogue chromosomal and plasmid genes implicated in AMR. The core genome multi-locus sequence typing (cgMLST) approach was used for comparative genomics analysis. In vitro resistance measured by disc diffusion revealed that 100%, 92.8% and 89.3% of the isolates were resistant to tetracycline, penicillin and ciprofloxacin, respectively; while for the E-test the method, 100%, 91.0% and 85.7% were recorded, respectively. A total of 22 sequence types (STs) were identified by multilocus sequence typing (MLST), with ST-14422 (n=10), ST-1927 (n=8) and ST-11210 (n=7) being the most prevalent. Six novel STs were also identified (ST-15634, 15636-15639 and 15641). All isolates harboured chromosomal AMR determinants that confer resistance to beta-lactam antimicrobials and tetracycline. A single cefixime resistant strain that belonged to N. gonorrhoeae multiantigen sequence typing (NG-MAST) ST1407, a strain associated with widespread cephalosporin resistance was identified. Neisseria gonorrhoeae Sequence Typing for Antimicrobial Resistance (NG-STAR) AMR typing identified 29 unique sequence types, with ST-464 (n=8) and the novel ST-3366 (n=8) being the most prevalent. Notably, 20 of the 29 STs were novel, indicative of the unique nature of molecular AMR determinants in the Ghanaian strains. Plasmids were highly prevalent: pTetM and pblaTEM were found in 96% and 92% of isolates, respectively. The TEM-135 allele, which is an amino acid change away from producing a stable extended-spectrum β-lactamase that could result in complete cephalosporin resistance, was identified in 28.5% isolates. Using WGS, we characterized N. gonorrhoeae strains from Ghana, giving a forecast of the possible state of gonococci AMR in the near future and highlighting the need for constant genomic surveillance.